Study the factors affecting customer’s decision to purchase Laundry detergent in traditional markets in hanoi - Thai, Thi Xuan (2020)
This topic limits the scope of research in the Hanoi city market because Hanoi city is the economic hub of the country where have vibrant and competitive retail market. The competition between the traditional and modem retail channels is acute, thus ensuring that the results of research can representative for the research environment in Vietnam. The survey respondents in this study are consumers over 18 who used to buy laundry products at traditional markets in Hanoi. I would like to thank all the respondents that provided feedback as well as evidence on the various issues addressed in this report. Traditional markets in the study are limited to type 1, type 2 and type 3 markets in Hanoi City area, and are general markets classified in the form of retail , excluding specialized markets and wholesale markets. Limited form of the market helps to ensure the characteristics of the traditional retail channel in relation to the modem retail channel. The duration of the study is from October 2017 to the beginning of December 2017.